MODEL SINERGI KELEMBAGAAN DALAM PENINGKATAN KEWIRAUSAHAAN MAHASISWA DI UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Gustina Siregar; DEWI ANDRIANY; LILA BISMALA; YUDHA ANDRIANSYAH PUTRA (-)
The existence of Small and Medium Enterprises (UKM) in the Indonesian economy has a big role and potential in developing the national and sectoral economy absorbing a large number of workers. The development of UKM in the university environment is one of the responsibilities of the university and is a necessity to involve universities as a driving force for the emergence of young entrepreneurs in the campus environment. The Muhammadiyah University of North Sumatra has formed a special institution that deals with student entrepreneurship issues, namely PUSKIIBI (Center for Entrepreneurship Innovation and Business Incubator). The research was conducted using the independent interview method, collecting institutional documents and institutional policies, and information related to student activities. From the data set and information, the formulation is carried out. Model of Institutional Synergy in Student Entrepreneurship Development at UMSU. This study aims to determine what institutions and the involvement of these institutions in supporting the progress of entrepreneurship in umsu and to create a model of institutional synergy that directly or indirectly synergizes with Puskiibi. From the research results obtained 1) the role of puskiibi as incubator is, access to community and business networking, support from experienced mentors, validation of ideas, infrastructure assistance, access to investors. 2) Related institutions that support the success of student entrepreneurship are SRCC, Study Programs in UMSU, LP2M, Halal Studies Center, and Haki Center. 3) The synergy model that must be developed is the recruitment of start-up candidates obtained from PKM-K participating students who have been netted by SRCC, student essays with downstream potential and student entrepreneurship independent campus participants obtained from Prodi, research lecturers with industrial potential from LP2M and alumni who come to register directly at PUSKIIBI. Furthermore, PUSKIIBI provides assistance, the certificate is only in synergy with the UMSU Halal Study Center and for the management of Trademarks and Patents through the UMSU HAKI Center.